Profitability level of betel leaf (Piper betel L.) cultivation in some selected sites of Bangladesh - Islam, QMS; Matin, MA (Bangladesh Journal of Agricultural Research, 2017)
The study was conducted in three betel leaf growing districts, namely Noakhali, Rajbari and Khulna during 2015-16 to assess the agronomic practices, profitability and to explore the constraints to betel leaf cultivation. The study revealed that betel leaf cultivation was profitable, although benefit cost ratio (BCR) in the first and second year were below one due to high investment cost and low yield. The highest yield and gross return were received by the farmers in the fourth year. The BCR was found highest in fourth year followed by third year and fifth year. The BCR at 12%, 15% and 20% rate of interest were 1.16, 1.15 and 1.14, respectively. IRR was 59% in current situation, 42% by 5% decrease of return and 52% by 5% increase of cost. The result indicated that betel leaf cultivation was profitable under changing situation of sensitivity analysis. Farmers faced some constraints like leaf rot disease, high price of boroj materials, non-availability of modern variety, low price of betel leaf, high price of oilcake, vine died, lack of capital, etc. Therefore, breeders should take initiative to develop high yielding varieties of betel leaf and pathologist may conduct research on betel leaf for controlling diseases. Bangladesh J. Agril. Res. 42(2): 343-351, June 2017